Design of an Intelligent Lotus Root Node Cutting Machine Control System Based on PLC and Machine Vision1 - Zhang, Jianke; Sun, Ruicheng; Li, Tongyu; Lü, Xiaoqi; Liu, Hui (Scientific Journal of Technology, 2026)
Aiming at the problems of traditional lotus root processing, such as reliance on manual labor, low efficiency, and poor accuracy in node cutting, this paper designs an intelligent lotus root node cutting machine control system based on PLC and machine vision. The system integrates three modules: motion control, vision inspection, and human-machine interaction. With Siemens S7-200 SMART PLC as the control core, it handles logic decision-making and motion control. The Jetson Nano embedded platform equipped with the YOLOv5s object detection algorithm is used to identify and locate lotus root nodes in real time, and the position information is transmitted to the PLC via Socket communication. Based on this, the PLC drives the stepper motor to precisely control the cutting tool to complete node removal. Meanwhile, the system is equipped with a human-machine interface based on a Weinview touch screen, enabling status monitoring, parameter setting, and multi-level permission management. Experimental results show that the system achieves a node recognition accuracy of 92% and a processing speed of 6 nodes per minute. It features low cost, easy implementation, and stable operation, providing an effective intelligent solution for lotus root deep processing in small and medium-sized enterprises.